Mutation in SSUH2 Causes Autosomal‐Dominant Dentin Dysplasia Type I. Issue 1 (19th October 2016) - Xiong, Fu; Ji, Zhisong; Liu, Yanhui; Zhang, Yu; Hu, Lingling; Yang, Qi; Qiu, Qinwei; Zhao, Lingfeng; Chen, Dong; Tian, Zhihui; Shang, Xuan; Zhang, Leitao; et al.
Abstract : Dentin dysplasia type I (DDI) is a genetic disorder resulting from dentin defects. The molecular basis of DDI remains unclear. Here in, we mapped the gene locus responsible for DDI to 3p26.1–3p24.3 and further identified a missense mutation, c.353C>A (P118Q) in the SSUH2 gene on 3p26.1, which co‐segregated with DDI. The experimental results in vitro and in vivo demonstrated that SSUH2 disrupts dental formation and that this novel gene, together with other odontogenesis genes, is involved in tooth development. ABSTRACT: Dentin dysplasia type I (DDI) is an autosomal‐dominant genetic disorder resulting from dentin defects. The molecular basis of DDI remains unclear. DDI exhibits unique characteristics with phenotypes featuring obliteration of pulp chambers and diminutive root, thus providing a useful model for understanding the genetics of tooth formation. Using a large Chinese family with 14 DDI patients, we mapped the gene locus responsible for DDI to 3p26.1–3p24.3 and further identified a missense mutation, c.353C>A (p.P118Q) in the SSUH2 gene on 3p26.1, which co‐segregated with DDI. We showed that SSUH2 (p.P118Q) perturbed the structure and significantly reduced levels of mutant (MT) protein and mRNA compared with wild‐type SSUH2 . Furthermore, MT P141Q knock‐in mice (+/− and −/−) had a unique partial obliteration of the pulp cavity and upregulation or downregulation of six major genes involved in odontogenesis: Dspp, Dmp1, Runx2, Pax9, Bmp2, and Dlx2 . The phenotype of missing teeth was determined in zebrafish with morpholino gene knockdowns and rescued by injection of normal human mRNA. Taken together, our observations demonstrate that SSUH2 disrupts dental formation and that this novel gene, together with other odontogenesis genes, is involved in tooth development.